B‐cell lymphoblastic lymphoma of the nictitating membrane as the first presenting sign in a 2‐year‐old Springer Spaniel. Issue 11 (12th October 2018) - Holm, Frederik; Hardon, Tommy; Clasen‐Linde, Erik; Hjorth Mikkelsen, Lauge; Heegaard, Steffen
Key Clinical Message: B‐cell lymphoblastic lymphoma is an aggressive malignant disease. Necropsy and microscopical examination revealed widespread disease with a high proliferation index. This is the first reported case of B‐cell lymphoblastic lymphoma presenting in the ocular region and only the second reported lymphoma of the nictitating membrane. Abstract : B‐cell lymphoblastic lymphoma is an aggressive malignant disease. Necropsy and microscopical examination revealed widespread disease with a high proliferation index. This is the first reported case of B‐cell lymphoblastic lymphoma presenting in the ocular region and only the second reported lymphoma of the nictitating membrane.